Marianne Johansen: Middelalderbyen Køge. (1986). Hans Krongaard Kristensen: Middelalderbyen Viborg. (1987). Aage Andersen: Middelalderbyen Næstved. (1987). Anemette S. Christensen: Middelalderbyen Odense. Med bidrag af Per Kr. Madsen. (1988). - Degn, Ole (Historie/Jyske Samlinger, 1989)
Marianne Johansen: Middelalderbyen Køge. (Centrum, 1986). 109 s. Hans Krongaard Kristensen: Middelalderbyen Viborg. (Centrum, 1987). 155 s. - Aage Andersen: Middelalderbyen Næstved. (Centrum, 1987). 129 s. - Anemette S. Christensen: Middelalderbyen Odense. Med bidrag af Per Kr. Madsen. (Centrum, 1988). 204 s.